2023
DOI: 10.1371/journal.pone.0284760
|View full text |Cite
|
Sign up to set email alerts
|

Large hydropower projects increase stress despite compensation efforts: Evidence from the Brazilian Amazon

Abstract: Large hydropower projects continue to be built in developing nations, despite their known negative impacts. Large-scale energy projects strain local infrastructure and reduce access to infrastructure for households that live near them. Here we investigate the link between large-scale hydropower projects and stress. Our results suggest that these projects create stress through two mechanisms: strains on community resources and through the process of displacement. We also ask how compensation and resettlement pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…However, this argument obscures the severity of the adverse socio-environmental issues that occur during and remain after construction [6,30]. Among these issues, previous studies revealed that hydropower dams constructed in the Amazon region have resulted in increased stress among local populations [31]. Furthermore, they have been associated with the erosion of social capital [32] and a decrease in self-rated health [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, this argument obscures the severity of the adverse socio-environmental issues that occur during and remain after construction [6,30]. Among these issues, previous studies revealed that hydropower dams constructed in the Amazon region have resulted in increased stress among local populations [31]. Furthermore, they have been associated with the erosion of social capital [32] and a decrease in self-rated health [33].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, mosquito-borne diseases like dengue, chikungunya, and Zika (Lowe et al, 2020) pose further health risks. Furthermore, the construction of extensive infrastructure projects, such as roads and hydropower dams, increases the risk of diseases such as AIDS and leishmaniasis, along with heightened population stress (Barcellos et al, 2019;Johansen et al, 2023;Mayer et al, 2023).…”
mentioning
confidence: 99%